Changes in Serum Cytokine Levels in Active Tuberculosis With Treatment - Figen Deveci; H. Handan Akbulut; Teyfik Turgut; M. Hamdi Muz (Hindawi Limited, 2005)
It has been reported that IFN-γ, TNF-α, and IL-12 stimulate, and that IL-10, TGF-β, and IL-4 suppress the protective immune response against tuberculosis. We aim to evaluate changes in the serum levels of pro and antiinflammatory cytokines in active pulmonary tuberculosis (APTB) and the possible effects of treatment on these changes. Serum IL-12p40, IL-4, IL-10, TNF-α, IFN-γ, and TGF-β1 levels were determined in 20 APTB cases (group 1) before and 2, 4, and 6 months after therapy. The same parameters were also determined in 9 inactive pulmonary tuberculosis (IPTB) cases (group 2) and 9 healthy controls (HC, group 3). Before treatment, the mean serum IFN-γ, TNF-α, and IL-10 levels in group 1 were statistically higher than those in group 2 (P=.001, P=.024, P=.016, resp) or group 3 (P=.003, P=.002, P=.011, resp). The levels in group 1 decreased significantly after treatment (P=.001 for IFN-γ, P=.004 for TNF-α, P=.000 for IL-10). The serum levels of IL-12p40 were significantly higher in group 1 than in group 3 (P=.012) and decreased insignificantly after treatment. There was no difference in serum IL-4 and TGF-β1 levels among the groups (P>.05). Because the serum IL-12p40, IL-10, TNF-α, and IFN-γ levels were high in APTB, we believe that these cytokines have important roles in the immune response to Mycobacterium tuberculosis (M tuberculosis). These parameters could be used in follow-up as indicators of the success of APTB therapy.